Digital cultural transformation and tax incentive: the effect on business continuity of MSMEs during the covid-19 pandemic - Mei Rani Amalia; Yuniarti Herwinarni (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
This research aims to determine the effect of digital culture transformation and tax incentive policies on the sustainability of small and medium micro enterprises in Tegal City during the Covid-19 pandemic. The population in this study is food MSMEs who already have an active Instagram social media, have P-IRT and halal MUI, and are under the auspices of the Tegal City Manpower and Industry Office obtained a sample of 60 MSMEs. The data analysis technique used is multiple linear regression analysis. The results showed a significant effect of digital culture transformation and tax incentives on the continuity of Tegal City Micro, Small, and Medium Enterprises during the Covid-19 pandemic, partially and simultaneously.